The herbal and dietary supplement blind spot: why standard drug screening tools aren't enough? - Sha’ari, Mohammad Suhaidi; Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
Despite the growing prevalence of herbal and dietary supplement (HDS) use, existing drug-related problem-screening tools remain alarmingly inadequate in detecting risks linked to HDS. As more patients self-prescribe these products, this gap in detection becomes a critical threat to patient safety.